Expert Answers

durbanville | Certified Educator

-12+x=50

To solve we need to get x by itself. Therefore add 12 to both sides:

+12 -12 +x = 50 +12

`therefore x= 62`

To check, substitute this value into the original equation:

-12 + (62) = 50

50 = 50

`therefore` **x=62 is correct. **

Further Reading:

Student Comments

taangerine | Student

-12+x=50

To solve:

- Rewrite: x+(-12)=50
- Simplify: x-12=50
- Since it is subtraction, what is the opposite operation for it? (addition) -- Add 12 on both sides to isolate 'x': x-12
**+12**=50**+12** - Simplify: x=62

- Plug 62 in for 'x' in the original equ: -12+62=50
- Solve -12+62.
- Since -12+62 is 50, the statement is true.
- 50=50

jess1999 | Student

-12 + x = 50

To solve this , first add 12 on both sides

By adding 12 on both sides , you should get

**x = 62 **which is your answer for " x "

Now to check :

Plug in 62 as " x "

-12 + 62 = 50 subtract -12 with 62

50 = 50

user8231205 | Student

-12+x=50

+12 +12

x=62

You just add the farthest number away from x to the other side.